KREASI SULAMAN SUJI CAIA MENGGUNAKAN TEKNIK KERANCANG TIMBUL UNTUK PAKAIAN PEREMPUAN MINANGKABAU - Silva Yusalim; Susas Rita Loravianti; Nursyirwan Nursyirwan (Melayu Arts and Performance Journal, 2021)
The creation of “Suji Caia's embroidery creations using engineering techniques. Embossed for Minangkabau Women's Clothing” is a collaboration of Suji Caia with a manual draft embossed using gold / silver thread metallic. This Suji Caia embroidery creation is applied to Minangkabau women's clothing in the form of a veil, baju kurung and a bag. The form of this is the creation with the concept of expressing personal art as a symbol of the author's personal expression of Suji Caia. This creation is a work of textile art which is applied to Minangkabau women's clothing using rose and saik galamai motifs. In this work, the use of sequins, swarosvky and crystal crest are additional techniques used to add beauty value to the work. There are several stages in creating this artwork method, including exploration, design and embodiment stages. As a result, five works were created, the Minangkabau women's clothing set paired with Pandai Sikek songket.Keywords: Suji Caia Embroidery; Embroidery; Design, Minangkabau; Women's ClothingAbstrakPenciptaan karya seni “Kreasi Sulaman Suji Caia menggunakan Teknik Kerancang Timbul untuk Pakaian Perempuan Minangkabau” merupakan kolaborasi Suji Caia dengan kerancang manual berbentuk timbul menggunakan benang emas/ perak metalik. Kreasi Sulaman Suji Caia ini di terapkan pada pakaian perempuan Miunangkabau berupa kerudung, baju kurung dan tas. Bentuk karya ini merupakan hasil kreasi pengkarya dengan konsep ekspresi personal seni sebagai lambang ekspresi pribadi pengkarya terhadap Suji Caia. Kreasi ini merupakan karya seni tekstil yang diaplikasikan pada pakaian perempuan Minangkabau menggunakan motif mawar dan motif Saik Galamai. Dalam karya ini pemasangan payet, swarosvky dan jambul Kristal merupakan teknik tambahan yang dipakai untuk menambah nilai keindahan karya. Metode dalam penciptaan karya kriya seni ini melalui beberapa tahap, antaranya tahap eksplorasi, perancangan, dan perwujudan. Karya yang diciptakan berjumlah lima set pakaian perempuan minang yang dipasangkan dengan songket Pandai Sikek.Kata Kunci: Sulaman Suji Caia; Bordir, Kerancang; Pakaian Perempuan; Minangkabau.